Elevated Carcinoembryonic Antigen at the Time of Recurrence as a Poor Prognostic Factor in Colorectal Cancer: A Propensity Score Matching Analysis - Shin, Jung Kyong; Huh, Jung Wook; Lee, Woo Yong; Yun, Seong Hyeon; Kim, Hee Cheol; Cho, Yong Beom; Park, Yoon Ah (Frontiers in Oncology, 2022)
There are few studies on the prognostic impact of CEA level at the time of recurrence in recurrent colorectal cancer. The objective of this study was to evaluate the prognostic value of serum CEA levels at the time of recurrence in patients with recurrent colorectal cancer. Between 2007 and 2014, 962 consecutive recurrent patients for colorectal cancer were analyzed. These patients were divided into two groups according to CEA level at the time of recurrence (r-CEA): high r-CEA (≥5 ng/ml) (n = 428) and normal r-CEA (<5 ng/ml) (n = 534). The prognostic effects of r-CEA were evaluated by one-to-one propensity score matching (PSM) to adjust factors between groups. After matching, a total of 778 patients, 389 per group, were analyzed. After matching, the 5-year disease-free survival rate for the high r-CEA group was significantly lower than that for the normal r-CEA group. The 5-year overall survival rate was 56.5% in the high r-CEA group and 66.0% in the normal r-CEA group (p = 0.008). The 5-year cancer-specific survival rate was 61.7% in the high group and 67.5% in the normal group (p = 0.035). In a multivariate analysis of prognostic factors, high preoperative CEA level at the time of recurrence, poor histologic grade, and lymphatic invasion were associated with poorer overall survival. The high r-CEA level group showed significantly poorer prognosis than the normal r-CEA group. Therefore, the r-CEA level can be used as a prognostic factor in recurrent colorectal cancer. Aggressive adjuvant treatment needs to be considered for patients with an initially high CEA level and lymph node positivity who are prone to recurrence.